Prototype Of A Website-Based Visitor Data And Payment Management System At Universitas Ibn Khaldun Bogor - Setiawan, Foni Agus; Riana, Freza; Fadhilah, Muhammad Rifqi (Moneter: Jurnal Keuangan dan Perbankan, 2024)
The advancement of science and technology has led to the development of various systems aimed at aiding human life. One example is data management systems designed to handle and store data. Security is also a crucial aspect, especially in institutions. Many methods are used to ensure security, one of which is the use of gate barriers, such as those at Ibn Khaldun University in Bogor. Currently, the gates at Ibn Khaldun University use an automated system where the barrier opens and closes automatically as vehicles pass through. The gates are also integrated with a system. However, this system still has some shortcomings, such as not all visitors passing through the gate being identified and issues with the payment cycle. The method used in this research is the Rapid Application Development (RAD) method, which emphasizes speed in system development.